Scientific and technological prerequisites for improvement and industrial development of low-flow compressor units based on long-stroke piston stages - V. L. Yusha (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
An overview analysis of research and development in the field of air and refrigeration low-flow compressors based on low-speed long-stroke piston stages is presented and an assessment of scientific and technological prerequisites for improving their energy efficiency and competitiveness is carried out. Two promising directions are considered in which such compressors can find effective application: increasing the gas pressure from atmospheric pressure to medium and high pressures; implementation of combined processes of compression and condensation of refrigerants in the working chamber of the stage. A number of scientific problems have been proposed and substantiated, the solution of which will make it possible to create competitive compressor units applicable in refrigeration and cryogenic engineering, thermostatting and life support systems, medicine and pharmaceuticals, petrochemical and oil and gas industries, small-scale energy, transport.